PENGARUH PENEMPATAN KARYAWAN DAN PENILAIAN PRESTASI KERJA TERHADAP KINERJA KARYAWAN (KASUS BAGIAN ADMINISTRASI PTPN V SEI BUATAN) - Roiyah "; Seno Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted at PTPN V Sei Buatan whick located at Kecamatan Dayun Kabupaten Derah Tingkat II Siak Indrapura.This study aims to determine the effect of Placement and Performance appraisal work on the performance of employees of the administrasi PTPN V Sei Buatan.In this research the method used is descriptive quantitative with SPSS program software ver. 21 for windows. Populasi in this research is all administrative employees at PTPN V Sei Buatan (Palm Oil Mill) Kampung Sawit Permai Kecamatan Dayun Kabupaten Siak that is 52 all employess Samples taken based on method using accidental samping are 52 employees.methods of data collection using questionnaires and interview, This research used questionnaire with measurement scale that is Likert scale which analyzed by validity test, reliability test, simple regression analysis, multiple regression analysis, analysis of determination, t test, and f test.From the result of tests conducted show that placement have a significant effect on employees performance, job performance appraisal has a significant effect on employees performance, as well as placement and performance appraisal affect simultaneously to employee performance. The calculation results known R Squre is the coefficient of determination and obtained the value of R Squre of 0.761. That is, the work environment and organizational commitment affect employee job satisfaction of 76,1%.Keywords : Placement, Performance appraisal, employee performanc